Capnocytophaga cynodegmi bacteremia associated with a cat bite in a patient with systemic lupus erythematosus on hemodialysis: A case report - Masahiko Nakao; Naoto Hosokawa; Wang Ziren; Takeru Yamamoto; Yosuke Ebisu; Naoki Watanabe; Tomohisa Watari; Yoshihito Otsuka; Ryosuke Osawa (IDCases)
The genus Capnocytophaga, which is part of the oral microbiome of both humans and animals, has the potential to cause severe infections in humans following animal bites. A 59-year-old man with systemic lupus erythematosus (SLE) on hemodialysis presented with cellulitis of the left upper limb after being bitten by his cat and was admitted to our hospital. Blood cultures were obtained, and empiric treatment with ampicillin/sulbactam was initiated. The patient developed a non-severe drug eruption on the 3rd hospital day, prompting a switch to ceftriaxone. Thin spindle-shaped Gram-negative bacilli were isolated from the blood cultures 127 h (5 days and 7 h) after obtained blood sample, and the patient completed a 2-weeks course of ceftriaxone with complete recovery. The isolate was identified as Capnocytophaga cynodegmi by MALDI-TOF MS and 16S rRNA gene sequencing. This case highlights the importance of considering C. cynodegmi in cat bite-associated infections. Obtaining blood cultures and extending incubation periods may be crucial for identifying the causative pathogen and guiding appropriate treatment in such cases.